2012
DOI: 10.1007/s00774-012-0370-4
|View full text |Cite
|
Sign up to set email alerts
|

Smoking is a predictor of worse trabecular mechanical performance in hip fragility fracture patients

Abstract: Clinical risk factors (CRFs) are established predictors of fracture events. However, the influence of individual CRFs on trabecular mechanical fragility is still a subject of debate. In this study, we aimed to assess differences, adjusted for CRFs, between bone macrostructural parameters measured in ex-vivo specimens from hip fragility fracture patients and osteoarthritis patients, and to determine whether individual CRFs could predict trabecular bone mechanical behavior in hip fragility fractures. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Smoking was the strongest predictor for fixation failure in younger adults (p=0.025). Nonetheless, the bone mineral density in smokers and non-smokers is comparable 10 , because bone mineral density only indicates a lower bone mass rather than reduced trabecular mechanical property. In addition, smoking may affect collagen and healing of bone and tissues.…”
Section: Discussionmentioning
confidence: 93%
“…Smoking was the strongest predictor for fixation failure in younger adults (p=0.025). Nonetheless, the bone mineral density in smokers and non-smokers is comparable 10 , because bone mineral density only indicates a lower bone mass rather than reduced trabecular mechanical property. In addition, smoking may affect collagen and healing of bone and tissues.…”
Section: Discussionmentioning
confidence: 93%
“…Similar findings were reported in elderly women; former and current smokers compared to nonsmokers had increased risk for fracture [ 59 , 71 ], including nonvertebral fractures in patients with diabetes (OR = 3.47, 95%CI: 1.82-6.62, P = 0.001) [ 61 ]. Regardless of fracture site, six cohort studies and one case-control study examining both sexes found smoking was significantly associated with poor fracture outcomes, such as nonunion ( P < 0.01) [ 57 , 58 , 60 , 66 ], lower trabecular strength (beta = -0.323; P = 0.045) and toughness (beta = -0.403; P = 0.018) [ 68 ], and delayed mean healing time [ 64 ]. No significant association was found between fracture and delay in filling [ 69 ] work absenteeism (P = 0.1177) [ 66 ] or low mental and physical-function scores on the Short Form 36 (SF-36) [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…29 Moreover, smoking was an independent predictor of worse trabecular strength in hip fracture patients. 30 As for the indirect effect of smoking on bone health, smoking was associated with decreased levels of parathyroid hormone 31 and vitamin D, 32 which could undermine bone integrity.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, pernicious effects of smoking on bone mineralization and collagen synthesis were affected in a mouse model, demonstrating that mice exposed to cigarette smoke exhibited reduction of type I collagen deposition, which is critical for bone formation, which ultimately lead to slowed delayed bone formation rate [ 29 ]. Moreover, smoking was an independent predictor of worse trabecular strength in hip fracture patients [ 30 ]. As for the indirect effect of smoking on bone health, smoking was associated with decreased levels of parathyroid hormone [ 31 ] and vitamin D [ 32 ], which could undermine bone integrity.…”
Section: Discussionmentioning
confidence: 99%